Terminal Decline in Well-Being: The Role of Social Orientation - Denis Gerstorf; Christiane A. Hoppmann; Corinna E. Löckenhoff; Frank J. Infurna; Jürgen Schupp; Gert G. Wagner (Psychology and Aging, 2016)
Well-being development at the end of life is often characterized by steep deteriorations, but individual differences in these terminal declines are substantial and not yet well understood. This study moved beyond typical consideration of health predictors and explored the role of social orientation and engagement. To do so, we used social variables at the behavioral level (self-ratings of social participation) and the motivational level (valuing social and family goals), assessed 2 to 4 years before death. We applied single- and multiphase growth models to up to 27-year annual longitudinal data from 2,910 now deceased participants of the nation-wide German Socio-Economic Panel Study (Mage at death = 74 years; SD = 14; 48% women). Results revealed that leading a socially active life and prioritizing social goals in late life were independently associated with higher late-life well-being, less pronounced late-life decline, and a later onset of terminal decline. Significant interaction effects suggested that the combination of (reduced) social participation and (lowered) social goals magnifies the effects of each other. Findings also indicated that less decline in social participation was associated with less severe rates and a later onset of well-being decline. We found little evidence that valuing family goals is associated with late-life trajectories of well-being. Associations were independent of key correlates of well-being and mortality, including age at death, gender, education, disability, hospital stays, and goals in other life domains. We discuss possible pathways by which maintaining social orientation into late life may help mitigate terminal decline in well-being.
Additional information: This article may not exactly replicate the authoritative document published in the APA journal. It is not the copy of record which can be found at http://dx.doi.org/10.1037/pag0000072
Keywords: 330; development; successful aging; life satisfaction; social support; German Socio-Economic Panel Study; Alter; Alternde Bevölkerung; Lebenszufriedenheit; Soziale Beziehungen; Soziales Netzwerk; Sterblichkeit